Evaluating bananas: A global partnership: results of IMTP phase II - Orjeda, G.; International Network for the Improvement of Banana and Plantain (2000)
For the International Musa Testing Programme (IMTP) Phase II, germplasm was evaluated for resistance to black Sigatoka (M. fijiensis), yellow Sigatoka (M. musicola) and Fusarium wilt (Fusarium oxysporum f. sp. cubense). The majority of IMTP Phase II trials were planted during 1996 and 1997. The first part of this publication provides a synthesis of final results. In the second part, full results are given for Sigatoka sites in Cameroon, Colombia, Costa Rica, Honduras, Nigeria, the Philippines, Tonga, and Uganda, and for Fusarium wilt (Foc) sites in Australia, Brazil, Honduras, Indonesia, Malaysia, the Philippines, South Africa, Spain, Taiwan, and Uganda.